The Chihuahua dog: A new animal model for neuronal ceroid lipofuscinosis CLN7 disease?. Issue 4 (13th January 2016) - Faller, Kiterie M.E.; Bras, Jose; Sharpe, Samuel J.; Anderson, Glenn W.; Darwent, Lee; Kun‐Rodrigues, Celia; Alroy, Joseph; Penderis, Jacques; Mole, Sara E.; Gutierrez‐Quintana, Rodrigo; Guerreiro, Rita J.
Abstract : Neuronal ceroid lipofuscinoses (NCLs) are a group of incurable lysosomal storage disorders characterized by neurodegeneration and accumulation of lipopigments mainly within the neurons. We studied two littermate Chihuahua dogs presenting with progressive signs of blindness, ataxia, pacing, and cognitive impairment from 1 year of age. Because of worsening of clinical signs, both dogs were euthanized at about 2 years of age. Postmortem examination revealed marked accumulation of autofluorescent intracellular inclusions within the brain, characteristic of NCL. Whole‐genome sequencing was performed on one of the affected dogs. After sequence alignment and variant calling against the canine reference genome, variants were identified in the coding region or splicing regions of four previously known NCL genes ( CLN6, ARSG, CLN2 [= TPP1 ], and CLN7 [= MFSD8 ]). Subsequent segregation analysis within the family (two affected dogs, both parents, and three relatives) identified MFSD8 :p.Phe282Leufs13*, which had previously been identified in one Chinese crested dog with no available ancestries, as the causal mutation. Because of the similarities of the clinical signs and histopathological changes with the human form of the disease, we propose that the Chihuahua dog could be a good animal model of CLN7 disease. © 2016 Wiley Periodicals, Inc. Abstract : A single pair deletion in MFSD8 ( =CLN7 ) results in neuronal ceroid lipofuscinosis in Chihuahua dogs. These dogs represent an excellent animal model opportunity for this poorly understood NCL form because they closely mimic the human phenotype of the disease.